Association of Birth Weight with Central and Peripheral Corneal Thickness in Adulthood-Results from the Population-Based German Gutenberg Health Study - Achim Fieß; Michael S. Urschitz; Susanne Marx-Groß; Markus Nagler; Philipp S. Wild; Thomas Münzel; Manfred E. Beutel; Karl J. Lackner; Norbert Pfeiffer; Alexander K. Schuster (MDPI AG, 2021)
Purpose: Low birth weight (BW) is associated with altered ocular geometry such as a steeper corneal shape in adulthood. However, it is unclear whether low birth weight affects corneal thickness development in the center or periphery in adulthood which may contribute to ocular disease. The purpose of this study was to investigate corneal thickness in former low birth weight individuals in adulthood. Methods: The German Gutenberg Health Study is a prospective, population-based study in which every participant (age range 40-80 years) was measured with Scheimpflug imaging (Pentacam HR, Oculus Optikgeräte GmbH, Wetzlar, Germany). BW was collected by self-reports. The relationship between birth weight and corneal thickness at different locations were assessed. Linear regression models were carried out including uni- and multivariable analyses with adjustment for age, sex, mean corneal radius, and white-to-white distance. Main outcome measures were corneal thickness at the apex, at the pupil center, and at the corneal periphery. Results: Overall, 5657 participants were successfully measured (3019 females, aged 56.0 ± 10.3 years). In multivariable analyses a lower BW was associated with a thinner corneal thickness at the apex (B = 1.71 µm/500 g, p < 0.001) and at the pupil (B = 1.69 µm/500 g, p < 0.001). These effects diminished towards the corneal periphery resulting in no differences in the perilimbal regions. Conclusion: The present study provides evidence that lower birth weight goes along with corneal thickness alterations even into adult ages of 40 to 80 years. Thinner measurements of the cornea were particularly found in the corneal center and diminished in the periphery. This indicates that there may be fetal origins affecting corneal thickness development particularly in the corneal center.